Secondary School Students' Views on Environmental Pollution - Metin Akdoğan; Elif Alkar (Educational Academic Research)
In this study, secondary school students' views on environmental pollution were focussed. The participant group consisted of 5th, 6th, 7th, and 8th grade students (52 girls-55 boys) studying in Hakkâri city centre. In the qualitative study design, the Word Association Test (WAT) was used as a data collection tool. Descriptive analysis technique was used to analyse the data, and frequency and percentage charts were presented in the form of cut-off points (CP). In the results obtained, it can be stated that students have knowledge about the causes and consequences of environmental pollution. Although some answers responded to the types of environmental pollution (air pollution, water pollution, etc.), most answers shed light on the causes of pollution (garbage, ped bottle, etc.). Students' mental construction of environmental pollution is mostly based on wastes that take a long time to disappear in nature. In addition, some expressions that are far from the possible definitions and adjectives of environmental pollution show that they have cognitive knowledge deficiencies. In the study, the importance of education and training services on environmental pollution, especially on the impact of polluting wastes both regionally and globally, starting from early childhood, comes to the fore. Based on the results achieved, identification of misconceptions students have towards environmental pollution and conducting educational activities to eliminate this misconceptions could be recommended. In addition, which metaphors students relate the concept of garbage that they express the most could be researched.